If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 5)(x + 3) = 7 Reorder the terms: (5 + 3x)(x + 3) = 7 Reorder the terms: (5 + 3x)(3 + x) = 7 Multiply (5 + 3x) * (3 + x) (5(3 + x) + 3x * (3 + x)) = 7 ((3 * 5 + x * 5) + 3x * (3 + x)) = 7 ((15 + 5x) + 3x * (3 + x)) = 7 (15 + 5x + (3 * 3x + x * 3x)) = 7 (15 + 5x + (9x + 3x2)) = 7 Combine like terms: 5x + 9x = 14x (15 + 14x + 3x2) = 7 Solving 15 + 14x + 3x2 = 7 Solving for variable 'x'. Reorder the terms: 15 + -7 + 14x + 3x2 = 7 + -7 Combine like terms: 15 + -7 = 8 8 + 14x + 3x2 = 7 + -7 Combine like terms: 7 + -7 = 0 8 + 14x + 3x2 = 0 Factor a trinomial. (4 + x)(2 + 3x) = 0Subproblem 1
Set the factor '(4 + x)' equal to zero and attempt to solve: Simplifying 4 + x = 0 Solving 4 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + x = 0 + -4 x = 0 + -4 Combine like terms: 0 + -4 = -4 x = -4 Simplifying x = -4Subproblem 2
Set the factor '(2 + 3x)' equal to zero and attempt to solve: Simplifying 2 + 3x = 0 Solving 2 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = 0 + -2 3x = 0 + -2 Combine like terms: 0 + -2 = -2 3x = -2 Divide each side by '3'. x = -0.6666666667 Simplifying x = -0.6666666667Solution
x = {-4, -0.6666666667}
| 6x-y+5=180 | | 7x-248+x+44=180 | | 30-4x=14 | | 5(x-7)=2(2-2x)-3 | | [9(x+5)-16]+[3(x-2)+4]= | | x+8-1/3=90/11 | | 2x^2+8x-192=0 | | 3x+(x*x)=180 | | 0.06(10-x)(100)= | | x^2-5x=x(5+x) | | x^2-5x=x(5x) | | 2x+55=272 | | (4y-7)+(-2y+5)= | | 2/5(x+3)=6 | | 3x+7-8(x+2)=-36 | | N(N-3)=700 | | 23-4x=9 | | 16x^4-54x= | | 9w-28=2 | | 4a-4=4x+4-2x | | 4t^2-16t+7=0 | | x^7+64x^4=0 | | 3y^2+17y-28= | | 6a+a-9=30 | | 7-5a=17 | | 2(4a+3)=8+6(2a-3) | | 8x-32=-8(4-5x) | | 7(3x-4)=59 | | 3x+-4=14 | | 2y+50+5y-17=180 | | 3[5(z-5)+17]-[3(5z-3)+3]= | | -(8*m+4)=4*m-2(6*m+2) |